Pemanfaatan Abu Batu Untuk Bahan Bangunan Batako, Paving Block Dan Roster - H. Listiawaty; I. K. Sulendra; T. Hilmansyah; M. Sutrisno (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Central Sulawesi is one of the main producers of Quarry C, which is processed into crushed stone in crushed stone factories (stone crushers). The number of crushed stone factories operating in the area between Palu-Donggala City is around forty units. The production of crushed stone factories apart from 1-2" and 2-3" crushed stone also contains smaller sized stone ash. This rock ash has a much smaller economic value so it is often not utilized and becomes waste at factory sites. Stone ash with the characteristics of a small specific gravity, even lighter than natural sand, has considerable potential to be used as a building material. It just needs research and testing before being used. Because it has a fine gradation and a small specific gravity, its potential can be used to make lightweight bricks, wall rosters and paving blocks. Apart from that, it is still possible to use it as a filler in asphalt concrete mixtures and aggregates for lightweight concrete. The initial tests required in the laboratory are: sieve analysis and compressive strength tests of bricks, paving blocks and rosters. The test results showed that there was an increase in compressive strength values for both bricks, paving blocks and roofs. The compressive strength value of brick with the addition of stone ash complies with SNI requirements and is included in category A, Paving Block is included in category A for road use, as well as roster there is a significant increase in the compressive strength value.